The influence of extended fasting on thyroid hormone: local and differentiated regulatory mechanisms - Sui, Xiukun; Jiang, Siyu; Zhang, Hongyu; Wu, Feng; Wang, Hailong; Yang, Chao; Guo, Yaxiu; Wang, Linjie; Li, Yinghui; Dai, Zhongquan (Frontiers in Endocrinology, 2024)
The hypometabolism induced by fasting has great potential in maintaining health and improving survival in extreme environments, among which thyroid hormone (TH) plays an important role in the adaptation and the formation of new energy metabolism homeostasis during long-term fasting. In the present review, we emphasize the potential of long-term fasting to improve physical health and emergency rescue in extreme environments, introduce the concept and pattern of fasting and its impact on the body's energy metabolism consumption. Prolonged fasting has more application potential in emergency rescue in special environments. The changes of THs caused by fasting, including serum biochemical characteristics, responsiveness of the peripheral and central hypothalamus-pituitary-thyroid (HPT) axis, and differential changes of TH metabolism, are emphasized in particular. It was proposed that the variability between brain and liver tissues in THs uptake, deiodination activation and inactivation is the key regulatory mechanism for the cause of peripheral THs decline and central homeostasis. While hypothalamic tanycytes play a pivotal role in the fine regulation of the HPT negative feedback regulation during long-term fasting. The study progress of tanycytes on thyrotropin-releasing hormone (TRH) release and deiodination is described in detail. In conclusion, the combination of the decrease of TH metabolism in peripheral tissues and stability in the central HPT axis maintains the basal physiological requirement and new energy metabolism homeostasis to adapt to long-term food scarcity. The molecular mechanisms of this localized and differential regulation will be a key research direction for developing measures for hypometabolic applications in extreme environment.